ConToVi: Multi‐Party Conversation Exploration using Topic‐Space Views. (4th July 2016) - El‐Assady, Mennatallah; Gold, Valentin; Acevedo, Carmela; Collins, Christopher; Keim, Daniel
Abstract: We introduce a novel visual analytics approach to analyze speaker behavior patterns in multi‐party conversations. We propose Topic‐Space Views to track the movement of speakers across the thematic landscape of a conversation. Our tool is designed to assist political science scholars in exploring the dynamics of a conversation over time to generate and prove hypotheses about speaker interactions and behavior patterns. Moreover, we introduce a glyph‐based representation for each speaker turn based on linguistic and statistical cues to abstract relevant text features. We present animated views for exploring the general behavior and interactions of speakers over time and interactive steady visualizations for the detailed analysis of a selection of speakers. Using a visual sedimentation metaphor we enable the analysts to track subtle changes in the flow of a conversation over time while keeping an overview of all past speaker turns. We evaluate our approach on real‐world datasets and the results have been insightful to our domain experts.